PENGARUH DIGITAL MARKETING, INOVASI PRODUK, DAN MODAL USAHA TERHADAP KEBERLANJUTAN UMKM PENGOLAHAN IKAN DI KECAMATAN PACIRAN KABUPATEN LAMONGAN - Sani Rusminah; Muhammad Imron Hamzah; Alfi Manzilatur Rohmah (CV. Armas Suan Sejahtera, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in fish processing in Paciran District, Lamongan Regency, face various challenges in maintaining business sustainability, especially in the digital era. Factors such as Digital Marketing, Product Innovation, and Business Capital are believed to play a significant role in helping MSMEs grow and survive amid increasingly fierce competition. This study aims to analyze the influence of Digital Marketing, Product Innovation, and Business Capital, both partially and simultaneously, and to identify the most dominant variable affecting the Business Sustainability of fish processing MSMEs. The research method used is quantitative with a descriptive approach. The sample consisted of 85 MSME actors, determined by random sampling method based on Hair et al.'s formula. Data analysis was performed using validity, reliability, classic assumption tests, and multiple linear regression with SPSS 30 software. The results show that Digital Marketing, Product Innovation, and Business Capital simultaneously have a positive and significant effect on business sustainability. Partially, Digital Marketing and Product Innovation have a positive and significant effect, while Business Capital is not significant. Product Innovation is the most dominant variable influencing the Business Sustainability of fish processing MSMEs in Paciran District